Mussolini and Fascism : The View from America - Diggins, John P. (Book collections on Project MUSE., 1972)
Mussolini, in the thousand guises he projected and the press picked up, fascinated Americans in the 1920s and the early '30s. John Diggins' analysis of America's reaction to an ideological phenomenon abroad reveals, he proposes, the darker side of American political values and assumptions.Originally published in 1972.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.